When Teaching Opened My Eyes: a Narrative Reflective Inquiry on Educational Inequality in a Rural Indonesian Village - Astuti, Renny Widia; Jannati, Rahmi Nasiti (Journal of English Education and Teacher Trainer, 2025)
This study presents a narrative reflective inquiry into the lived experience of a pre-service English teacher who volunteered in a rural village in Bogor, Indonesia. Through systematic reflection on teaching practice, this research examines educational inequality in remote areas where access to education often ends at the primary level. The narrative draws from reflective journals, photographs, and field observations collected during a two-week teaching program in Desa Cibuyutan. Grounded in reflective practice theory and critical pedagogy, this inquiry reveals how immersive teaching experiences shape pedagogical identity and deepen awareness of systemic educational inequities. The findings demonstrate that reflective narrative inquiry serves as a powerful tool for pre-service teachers to develop critical consciousness about rural-urban educational disparities and transform personal uncertainty into professional purpose. This study contributes to teacher education discourse by highlighting the value of experiential learning in preparing socially conscious educators committed to educational equity.